Alternatives for implementing efficiency conservation in the Imperial Irrigation District - Hatchett, Stephen, author; Bliesner, Ronald, author; Eckhardt, John R., author; Davids, Grant, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2008)
In 2003 the Imperial Irrigation District (IID), a 450,000-acre water district in Southern California, entered into a package of decisions and agreements known collectively as the Quantification Settlement Agreement and Related Agreements (QSA). As part of these agreements, IID agreed to a long-term transfer of water to the San Diego County Water Authority (SDCWA) and the Coachella Valley Water District (CVWD). According to the terms of the agreements, the water must come from conservation within IID. The transfer begins small but by 2026, IID must conserve and transfer 303,000 acre-feet of water each year or nearly 10% of its total annual water use. In 2007, IID completed the Efficiency Conservation Definite Plan that outlined strategies for both delivery system and on-farm water savings. IID examined a large number of alternatives to generate the savings. Alternatives differed largely according to two features: the mix of on-farm versus delivery system savings, and the structure of the on-farm incentive program. Seven different mixes of on-farm and delivery system savings were evaluated, ranging from the maximum practical delivery system savings to generating nearly all savings on-farm. Four different incentive program approaches appeared to be viable ways of inducing sufficient on-farm enrollment. The incentive approaches differed in the way that growers would be paid for their participation. The resulting alternatives varied significantly in their performance and cost-effectiveness. Costs included system conservation measures, payments to growers to implement on-farm measures, measurement and monitoring, and administration. System delivery savings of between 93,000 and 123,000 acre-feet per year provided the most cost-effective mix of savings. The complementary on-farm savings were 180,000 to 210,000 acre-feet per year, with average payments to growers between $245 and $300 per acre-foot saved. This paper, one of seven detailing the findings of the Definite Plan, describes the development and analysis of alternatives to implement the conservation program, and summarizes important findings on how best to design on-farm conservation incentives to achieve cost-effective, real water savings without encouraging fallowing.
Urbanization of irrigated land and water transfers
IID - alternatives for implementing efficiency conservation
Not digitized by CSUL Digital Services.
Presented at Urbanization of irrigated land and water transfers: a USCID water management conference on May 28-31, 2008 in Scottsdale, Arizona.